Optimization of an Efficient Method for Genomic DNA Extraction from (Vicia faba L) Leaves with High Contents of Inhibitor Compounds - Ahmed Shaaban,; Wagdi Ghaleb,; Hanan Abosalah,; Masoud Alsheebani,; Ghada Elragaihy,; Salem Hammud,; Elmundr Abughnia, (AlQalam Journal of Medical and Applied Sciences, 2026)
The extraction of high-quality plant DNA in large quantities is considered a difficult task in all plant molecular studies, which makes the extraction of high-quality DNA from plants containing high amounts of inhibitor compounds the main challenge for researchers. Therefore, three different DNA extraction methods (CTAB, SDS, and a mixture of CTAB and SDS) were used and tested for the purpose of obtaining the best method for DNA extraction from Faba bean (Vicia faba L) plant leaves at different plant ages (7, 14, and 30 days). The estimation of DNA quality and purity was conducted by the Nanodrop spectrophotometer and gel electrophoresis system. The results of the present study showed that among the three DNA extraction methods used in this study CTAB method was the best method for extracting DNA from leaves in different plant ages specially leaves at the age of 7 days, followed by the SDS and CTAB methods. The absorbance ratio of extracted DNA from leaves with 7 days’ age using the CTAB method was above 1.9. CTAB performance was good in the elimination of the effects of inhibitor compounds such as protein; this technique has the potential to be an effective protocol for DNA extraction using leaves tissue. The result of this study also proved that the mixture of SDS and CTAB methods produced DNA with acceptable purity, whereas the A260/A280 ratio of absorbance for extracted DNA from leaves with 7 days’ age by the SDS+CTAB method treatment was 1.89. The results showed that the purity levels of extracted DNA from plant leaves at the age of 7 days were significantly higher than the other two treatments (14 and 30 days) in all the used methods, which explains that extracting DNA from young leaves is clearly successful. According to our result SDS method has an A260/A280 ratio of absorbance ranging from 1.53 to 1.87 in the treatment of leaves with 7 days’ age, whereas this range was lower than the CTAB method.